THE RELATIONSHIP BETWEEN THE IMPLEMENTATION OF ISLAMIC RELIGIOUS EDUCATION AND RELIGIOUS CULTURE IN PUBLIC SENIOR HIGH SCHOOLS OF THE MERANTI ISLANDS REGENCY - Hsb, Amrul Pahmi; Salm, Nola Fibriyanti Bte (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Purpose: This study aims to examine the relationship between the implementation of Islamic Religious Education (PAI) and the development of a religious school culture in two public senior high schools in the Meranti Islands Regency, namely SMA Negeri 3 Tebing Tinggi and SMA Negeri 2 Tebing Tinggi. Method: Using a quantitative correlational approach, data were collected from 224 respondents consisting of 212 students, 10 PAI teachers, and 2 principals. Research instruments included Likert scale questionnaires, observation guidelines, and semi-structured interviews. Result: Statistical analysis using SPSS version 26 showed a strong and significant positive correlation (r = 0.62, p < 0.01) between PAI implementation and the schools’ religious culture. Regression analysis revealed that PAI implementation contributes 38.4% to the formation of a religious culture, while other factors such as school leadership, family involvement, and community environment account for the remaining variance. Conclusion: Comparative results indicated that SMA Negeri 3 demonstrated a stronger correlation (r = 0.65) than SMA Negeri 2 (r = 0.58), suggesting contextual differences in institutional support and teacher engagement. Implication: The study contributes to the field of Islamic education by emphasizing that effective PAI implementation is not limited to classroom instruction but also reinforces religious habits and values through consistent practice and role modeling within the school ecosystem.